Estimating species-based community integrity under global warming, with special reference to the western Mediterranean region - Box, E O; Choi, J N (PHYTOCOENOLOGIA, 2000)
Climate-based estimates of the fitness of the main structural elements of several western Mediterranean plant communities were used to estimate potential community integrity and its consequent vulnerability under a global-change scenario involving warming but no net drying. Results for a simple Quercus ilex community suggest expansion northward and inland under warming but with significant loss of area currently covered by the community. The data for estimating such changes in potential community integrity and areal coverage can be readily obtained from climatic envelope models. Mapping can be done by interpolation or by pixel-based GIS methods.
Keywords: climatic envelope; community integrity; global war